Listening to Mozart Improves Current Mood in Adult ADHD – A Randomized Controlled Pilot Study - Zimmermann, Marco Bernd; Diers, Katerina; Strunz, Laura; Scherbaum, Norbert; Mette, Christian (Frontiers in Psychology, 2019)
Emotional lability is a common problem in adult patients with ADHD and is usually treated with methylphenidate. It is generally known that music can be used to improve mood in healthy adults. Therefore, this study was conducted to test the suitability of music as a possible non-pharmacological measure to improve mood. 40 patients with ADHD and 44 healthy control subjects were randomly assigned to one of two experimental conditions. The first group (music group) listened to Mozart’s music (KV 448) for 10 minutes while the second group remained in a silent room for 10 minutes (silence group). Subjective arousal and mood were assessed using self-report questionnaires before and after each condition. We showed that music listening led to a decrease in negative mood (sadness and hopelessness) in the ADHD group as well as in healthy controls. This effect was not evident in both silence groups.